The Effect of Work Facilities on Employee Performance in the Process of Clearance in and Clearance Out Arrangement of Ship Agency at PT. Bahari eka Nusantara Samarinda Branch - Desamen Simatupang; Tristanti Tristanti; Yonas Vieri (Dinasti Publisher, 2022)
Work facilities must be a concern of each organization because they can affect the overall performance of employees in a company / organization, as one of the agencies that pay attention to the performance of their employees and prepare work facilities that support the implementation of the Main Duties and Functions (TUPOKSI) of each employee. Meanwhile, the duties and functions of the ship agency, one of which is the process of managing clearance in and clearance out. The success of an enterprise can be viewed from the results of the work done by its employees. As explained above, the factor to improve employee performance is work facilities. With work facilities, it is possible to improve employee performance in order to achieve the goals that have been determined by managers with all potential effectively and efficiently. The purpose of this study was to determine the effect between work facilities on employee performance in the process of managing clearance in and clearance out of the ship agency. The approach method used is a descriptive quantitative method, while the data collection technique uses documentation, observation, and questionnaires so that the influence of work facilities can be found on employee performance. The results of this study show that there is an influence between work facilities on employee performance in the process of managing clearance in and clearance out of the ship agency.